1995
DOI: 10.1099/13500872-141-7-1683
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium meliloti lacking mosA synthesizes the rhizopine scyllo-inosamine in place of 3-O-methyl-scyllo-inosamine

Abstract: The Rhizobium meliloti Rm220-3 MOS locus producing the rhizopine scylloinosamine (Sr) in nodules is shown to consist of three ORFs (ORF1, mosf? and mosC) arranged in an operon structure. This differs from the R. meliloti L5-30 mos locus, which produces 3-0-methyl-scyllo-inosamine (3-0-MSI), by the complete absence of mosA. The deletion covers a region of 1235 nt and includes the entire MOSA gene as well as the sequence both upstream and downstream. As a result, Rm220-3 mos ORFl shares a 5' region common with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Our sequence analysis suggests that MOSA is closely related to DHDPS. Rao et al (1995) have shown that R. melitoti strains that lack the mosA gene produce the rhizopine scyllo-inosamine, whereas those that contain the mosA gene produce the rhizopine 3-o-methyl-scyllo-inosoa-mine. On this basis they argue that the probable role of MOSA is the methylation of scyllo-inosamine rather than the condensation of pyruvate to inositol (Murphy et al, 1993 (Kuhm et al, 1993).…”
Section: P¯anking Motif Is Taken By Janec ïEk As Possible Evidencmentioning
confidence: 98%
See 1 more Smart Citation
“…Our sequence analysis suggests that MOSA is closely related to DHDPS. Rao et al (1995) have shown that R. melitoti strains that lack the mosA gene produce the rhizopine scyllo-inosamine, whereas those that contain the mosA gene produce the rhizopine 3-o-methyl-scyllo-inosoa-mine. On this basis they argue that the probable role of MOSA is the methylation of scyllo-inosamine rather than the condensation of pyruvate to inositol (Murphy et al, 1993 (Kuhm et al, 1993).…”
Section: P¯anking Motif Is Taken By Janec ïEk As Possible Evidencmentioning
confidence: 98%
“…The reactions catalysed by these enzymes are summarised in Figure 1. A ®fth and tentative member of the family is the MosA protein (MOSA; Murphy et al, 1993;Rao et al, 1995), which is thought to Figure (Eaton & Chapman, 1992;Jeffcoat et al 1969b …”
Section: ; (3) Trans-o-hydroxybenzylidenepyruvatementioning
confidence: 99%
“…One superfamily member, the mosA gene product (Rhizobium meliloti), functions in rhizopine biosynthesis, a biosynthetic pathway that has not been fully characterized (11). Whereas studies of a mosA Ϫ mutant suggest that the MosA protein catalyzes methylation of a hydroxyl group (12), this predicted function is unexpected since it cannot be readily associated with a mechanism involving a protonated Schiff base functioning as an electron sink, e.g. the use of ␣-ketobutyrate as a methyl group donor is unprecedented in enzymology.…”
Section: The Enolase Superfamily: Abstraction Of the ␣-Protons Of Carmentioning
confidence: 99%
“…Intriguingly, this region contains duplications of parts of the s 54 gene rpoN, a gene required for pnifH activity. Another copy of pnifH has been identified upstream of the mos operon in S. meliloti strains L5-30 (Murphy et al, 1988) and Rm220-3 (Rao et al, 1995). mos genes are involved in rhizopine production in these strains, but are absent from strain Rm1021.…”
Section: Promoter Duplication and Genome Adaptationmentioning
confidence: 99%